A High-Power Broadband Multi-Primary DAT-Based Doherty Power Amplifier for mm-Wave 5G Applications - Wang, Fei; Wang, Hua (IEEE journal of solid-state circuits, 2021)
Silicon-based millimeter-wave (mm-Wave) power amplifiers (PAs) with high power and high peak/back-off efficiency are highly desired to efficiently amplify multi-Gb/s 5G NR signals. This article presents a fully integrated high-power broadband linear Doherty PA with multi-primary distributed-active-transformer (DAT) power combining. We introduce a transformer-based impedance inverter for active load modulation and a multi-primary DAT structure for hybrid series and parallel power combining. Based on this, we propose a transformer-based Doherty combiner with more design freedom and a multi-primary DAT-based Doherty PA for simultaneous active load modulation and low-loss power combining. The EM simulation results demonstrate that the proposed DAT-based Doherty output network achieves very symmetric and balanced load impedances among all the main and auxiliary PA ports. As a proof of concept, a 24-30-GHz prototype PA is implemented in a 0.13- μ \text{m} SiGe BiCMOS process. The PA achieves 30.4% PAE max , 28.3-dBm P_{sat} , 30.2% PAE at 26.8-dBm P_{\mathrm {1\,dB}} , and 21.2% PAE at 6-dB back-off from P_{sat} at 28 GHz. Modulation measurement with single-carrier 64-QAM signals and 5G NR FR2 orthogonal frequency-division multiplexing (OFDM) signals has been demonstrated. For a 200-MHz 1-CC 5G NR FR2 64-QAM signal, the PA achieves 18.1-dBm P avg and 13.8% PAE avg with −25.1-dB rms EVM at 28 GHz.